The role of the curricula of the Faculty of Education at the University of Prince Sattam bin Abdul Aziz in the rehabilitation of female students to professions as well as teaching profession - Omar, Mona Taha Mohammed (Journal of Educational and Psychological Sciences, 2018)
The purpose of the research was to find out the role of the curricula of the Faculty of Education in Dulm at the University of Prince Sattam bin Abdul Aziz in the Islamic Studies and Arabic Language Departments in the rehabilitation of female students in professions besides the teaching profession, due to the large number of graduates and the lack of job opportunities for them. To the professions are available in the labor market through their studies, and was used questionnaire for the students of the two sections contains five axes in addition to the core data center dealt with the following: - Studying the student in the departments of Islamic studies and the Arabic language: -1 - enable them skills of proficiency in English writing and speaking - Computer - Ability to communicate - Problem solving - The art of management - Dialogue - Dealing with others 2- Empowers them to work in the fields of social service and courts - Civil service Media - Administrative work - Libraries - Tourism and voluntary organizations and entrepreneurship. Communication skills and other skills. 4 - The student wants to provide the curriculum with special skills can be acquired .. The results were reached: 1 - Curriculum in the two sections to provide the skills mentioned, because the study focuses on knowledge without skills. 2 - The student needs to master many skills lacking ... The study recommends the following: - Modifying the curriculum and include skills when the student can master the previous skills ’and allow them to practice extracurricular activities’ and the opportunity to practice hobbies.